2020
DOI: 10.1002/andp.201900449
|View full text |Cite
|
Sign up to set email alerts
|

Fermi Arcs and DC Transport in Nanowires of Dirac and Weyl Semimetals

Abstract: The transport properties and electron states in cylinder nanowires of Dirac and Weyl semimetals are studied paying special attention to the structure and properties of the surface Fermi arcs. The latter make the electric charge and current density distributions in nanowires strongly nonuniform as the majority of the charge density is accumulated at the surface. It is found that a Weyl semimetal wire also supports a magnetization current localized mainly at the surface because of the Fermi arcs contribution. By… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…where we again used (31). This rough estimate is in qualitative agreement with the numerical results.…”
Section: Conductivity In Case Of a Large Number Of Bulk Statessupporting
confidence: 81%
See 2 more Smart Citations
“…where we again used (31). This rough estimate is in qualitative agreement with the numerical results.…”
Section: Conductivity In Case Of a Large Number Of Bulk Statessupporting
confidence: 81%
“…For larger ξ, direct scattering between the valleys becomes strongly suppressed and the relaxation of µ + − µ − must go via surface states. Thereby the relaxation along the arcs and the scattering from surface to bulk is much faster than the scattering from bulk to surface, see (31). The scattering length l c is thus set by the bulk-surface scattering length l bs , which is proportional to the ratio…”
Section: Valley Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In their original article, P. O. Sukhachov et al [8] examines the transport properties and electron states in nanowires of Dirac and Weyl semimetals. Dirac quantum matter exhibits a four-fold symmetry.…”
Section: Doi: 101002/andp202000037mentioning
confidence: 99%
“…Most experiments on Weyl semimetals focus on the angle-resolved photoemission spectroscopy, in which the existence of FAs has been confirmed. There are also theoretical studies of the FA and its transport properties [40][41][42][43][44], like quasiparticle interference (QPI) [45,46]. Recent progress has also shown that the configurations of the FAs are sensitive to the details of the sample boundary [47][48][49], thus opening the possibility for engineering FAs and exploring their novel effects and potential applications through surface device fabrication and transport measurements.…”
Section: Introductionmentioning
confidence: 99%